Sistem Pendukung Keputusan Penentuan Penerima Bantuan Keuangan Korban Bencana Alam Menggunakan Metode AHP - Marice Hotnauli Simbolon; Sartana; Fauzi Haris Simbolon (LOFIAN: Jurnal Teknologi Informasi dan Komunikasi, 2026)
The AHP method is a way to break down complex multi-factor or multi-criteria problems into a hierarchy. The AHP method was first proposed by Thomas L. Saaty, a simple and efficient method for identifying solutions from a set of alternatives. In this study, all applicants for assistance obtained based on a predetermined quota are entitled to receive assistance with a size that matches the weight obtained from the AHP. The method used to solve this research problem uses the Analytical Hierarchy Process (AHP) method. The programming language used is Visual Basic, which is useful for processing data into information, and Cristal Report as a medium for reporting. This decision support system seeks priority recipients of financial assistance for victims of natural disasters. The application of the decision support system seeks solutions in determining the provision of financial assistance to victims of natural disasters with criteria for the category of casualties, damage categories, building types, and land status categories.